INTEGRATED CLASSROOM-CHATBOT EXPERIENCE : AN ALTERNATIVE SOLUTION FOR ENGLISH AS FOREIGN LANGUAGE LEARNERS - Dewi Sari Wahyuni (English Language Education and Current Trends (ELECT), 2022)
Both in traditional and online English as a Foreign Language (EFL) classroom, interactions between teachers and peers are indeed needed to practice the targeted language. However, in classes attended by a big number of mixed ability learners, these interactions can hardly as effective as is expected. Along with limited available time for studying more about the language in the classroom as Foreign Language Learning (FLL), learners rarely use the target language in their day-to-day life or interacting with a native speaker, and this lack completes its complexity. Therefore, the writer argues that integrating chatbot in the classroom as an alternative solution to cope with learners' lack of interactions using English in the classroom and real life. This paper is a position paper in which the writer presents her arguable opinion on why integrating chatbots in EFL learning can be an alternative solution.   REFERENCES Dale, R. (2016). The Return of The Chatbots. Natural Language Engineering, 22, 811-817. Fryer, L. K., Coniam, D., Carpenter , R., & L?pu?neanu, D. (2020, June). Bots for Language Learning Now: Current and Future Direction. Language Learning and Technology, 24(2), 8-22. Fryer, L., & Carpenter, R. (2006, September). Emerging Technologies: Bots as Language Learning Tools. Language Learning & Technology, 10(3), 8-14. Retrieved from http://llt.msu.edu/vol10num3/emerging Fryer, L., & Nakao , K. (2009). Assessing Chatbots for EFL Learner Use. JALT, (pp. 849-856). Tokyo. Goda, Y., Yamada, M., Matsukawa, H., Hata, K., & Yasunami, S. (2014). Conversation with a Chatbot before an Online EFL Group. Information and Systems in Education, 13(1), 1-7. Haristiani, N. (2019). Artificial Intelligence (AI) Chatbot as Language Learning Medium: An Inquiry. International Conference on Education, Science and Technology. IOP Publishing. Kerr, P. (2016, December 1). Chatbots. Retrieved from Adaptive Learning in ELT: https://adaptivelearninginelt.wordpress.com/2016/12/01/chatbots/ Kiely, Y. (2019, September 23). Chatbot Could Help Learners and Teachers in Language Education. Retrieved from The Chatbot: https://thechatbot.net/chatbots-language-education/ K?l?çkaya, F. (2020). Using a Chatbot, Replika, to Practice Writing Through Conversations in L2 English: A Case Study. In M. Kruk, & M. Peterson, New Technological Applications for Foreign and Second Language Learning and Teaching (pp. 221-238). Turkey: Burdur Mehmet Akif Ersoy University. Kim, N.-Y. (2016). Effects of Voice Chat on EFL Learners' Speaking Ability According to Proficiency Levels. Multimedia-Assisted Language Learning, 19(4), 63-88. Kim, N.-Y. (2019). A Study on the Use of Artificial Intelligence Chatbots. Journal of Digital Convergence, 17(8). Norton, M. (2020, August 11). Bots for Practising English Conversation Skills. Retrieved from World of Better Learning: https://www.cambridge.org/elt/blog/2020/08/11/bots-for-ractising-english-conversation-skills-part-1/?utm_source=wobl &utm_medium=blog&utm_ content= woblcontent &utm_campaign=general Pham, X. L., Pam, T., Nguyen, Q. M., Nguyen, T. H., & Cao, T. H. (2018). Chatbot as an Intelligent Personal Assistant for Mobile Language Larning. ICEEL (pp. 16-21). Bali: ACM. Syawar, B. A. (2017). Integrating CALL Systems with Chatbots as Conversational. Computación y Sistemas, 21(4), 615-626.